Activation of an elastase precursor by the lasA gene product of Pseudomonas aeruginosa. - Goldberg, J B (1987)
To study the role of the lasA gene product in the secretion of enzymatically active elastase by Pseudomonas aeruginosa, we constructed mutants by gene replacement with in vitro-derived insertion and deletion mutations in the cloned lasA gene. lasA mutants were deficient in the production of elastolytic activity. A membrane-associated, higher-molecular-weight (approximately 47,000) precursor of elastase was observed in both the wild-type and the lasA mutants. Unlike the wild-type strain, the lasA mutant accumulated the 47,000-molecular weight elastase species in the soluble fraction of the cell, suggesting that the lasA gene product has a role in elastase secretion. Although lasA mutants were deficient in elastolytic activity, they produced a proelastase with a mature molecular weight (approximately 37,000) that still retained general proteolytic activity. Final yields of elastase-related material were approximately the same in both the wild-type strain and lasA mutant supernatants. The lasA gene was expressed in Escherichia coli, and the approximate molecular weight of the lasA gene product was 31,000. Extracts of E. coli containing the lasA gene product were shown in vitro to activate the proelastase produced by P. aeruginosa lasA mutants to an enzyme with elastolytic activity. Thus the lasA gene product has a direct effect on broadening the substrate specificity of secreted proelastase, as well as a second role (direct or indirect) in the secretion of elastase.